Burden of Infectious Complications after Upper Extremity Allotransplantation: A Matched Cohort Study. (July 2018) - Conrad, Anne; Petruzzo, Palmina; Kanitakis, Jean; Gazarian, Aram; Badet, Lionel; Vanhems, Philippe; Thaunat, Olivier; Morelon, Emmanuel; Sicard, Antoine
Abstract : Introduction: Risk-to-benefit ratio of upper extremity allotransplantation (UEA), a non-vital transplantation procedure, remains to be clarified, as concerns have been raised regarding infectious, metabolic and malignant complications of lifelong immunosuppression. The aim of this study was to provide a relevant assessment of the infectious risk in UEA recipients. Infectious complications in UEA recipients were analyzed and compared to that of kidney transplant (KT) recipients who have the lowest rate of infections among the different populations of solid organ transplant recipients. Patients and Methods: Matched cohort study among UEA and KT recipients from the prospectively maintained "International Registry on Hand and Composite Tissue Transplantation" (IRHCTT) and the French "Données Informatisées et VAlidées en Transplantation" (DIVAT) database. All UEA recipients reported to the IRHCTT between 1998 and 2016 were matched with KT recipients (1:5), according to age (±5 years), sex, CMV serostatus of donor and recipient and (depleting or not depleting) induction. Incidence and characteristics of all infectious events reported to the databases at three posttransplant periods (0-6 months, 7-12 months, >12 months) were analyzed. Results and Discussion: Sixty-one UEA recipients were matched with 305 KT recipients. Mean (±SD) follow-up of UEA and KT recipients was 2583±1876 and 2230±1792 days, respectively (p=0.16). Immunosuppression regimen at 3 months posttransplant was similar. The number of acute rejection episodes during follow-up was higher in UEA recipients than in KT recipients (1.3±1.6 vs 0.4±0.7, p<0.01). During follow-up, 30 (50.8%) UEA recipients presented a total of 61 infectious events while 129 (42.3%) KT recipients presented 243 infectious events. Incidence rate of infectious events was higher in UEA recipients than in KT recipients during the first 6 months posttransplant (3.27 vs 1.95 events/1000 transplant-days, p=0.01). Thereafter, incidence rates of infections did not significantly differ between UEA and KT recipients: 0.61 vs 0.45 events/1000 transplant-days (7th-12th month posttransplant, p=0.5) and 0.15 vs 0.21 events/1000 transplant-days (>12th month posttransplant, p=0.11), respectively. Distribution of sites of infections was significantly different: while mucocutaneous infections predominated among UEA recipients at each of the three posttransplant periods (representing 28.6%, 50% and 30% of infectious events, respectively), urinary tract infections (28.6%, 23.8% and 33.9%) and pneumonia (17.3%, 42.9% and 28.2%) predominated among KT recipients. Conclusion: Incidence rate of infectious events is higher in UEA recipients than in KT recipients during the first 6 months posttransplant. After the first 6 months posttransplant, incidence of infections is low, at worst equivalent to the incidence observed in young KT recipients. Distribution of infectious syndromes suggests less severe infections in UEA than in KT recipients.